Diversifying diets and information sources - Ndiaye, Oumy Khairy (Technical Centre for Agricultural and Rural Cooperation, 2005)
Oumy Ndiaye of the Technical Centre for Agricultural and Rural Cooperation (CTA), talks about how the internet could be used to serve rural people, and nutritional information needed in her home country, Senegal.